Effects on Taxation on the Forecasting of Income Inequality: Evidence from Germany, Greece, and Italy - D’Amico, Guglielmo; Di Biase, Giuseppe; Manca, Raimondo (Panoeconomicus, 2013)
In this paper, we investigate the impact of the fiscal system on wealth redistribution in Germany, Greece, and Italy. We demonstrate the appli- cation of the model to the data of the quoted countries. We obtain the gross income distributions by starting from the net income distributions downloaded from the Eurostat website and by using the individual income tax rates of each country. We evaluate the Dynamic Theil’s Entropy that allows us to recover the total inequality between the net and gross income distributions for each of these countries. Such a comparison allowed us to understand how the fiscal systems affect wealth distribution. These results can be used for planning welfare policies. Key words: Income distribution, Dynamic Theil’s entropy, Fiscal system, Welfare policies. JEL: E64, E27.